2013
DOI: 10.2528/pier13050102
|View full text |Cite
|
Sign up to set email alerts
|

Direction Finding for Bistatic Mimo Radar Using Em Maximum Likelihood Algorithm

Abstract: Abstract-In this paper, we investigate an expectation-maximization (EM) maximum likelihood (ML) algorithm of direction finding (DF) for bistatic multiple-input multiple-output (MIMO) radar, where it is shown that the DF problem can be described as a special case of ML estimation with incomplete data. First, we introduce the signal and the noise models, and derive the ML estimations of the direction parameters. Considering the computational complexity, we make use of the EM algorithm to compute the ML algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…The performance of the proposed and spectrum averaging schemes was shown when they are using a 1000 MHz bandwidth with = 3.6 GHz, while Silva's method was presented at several frequencies since it is a narrowband-based angle estimation. The performance bound calculated from the Cramér-Rao bound (CRB) when the DOD and DOA of a stationary target are estimated individually [26,27] was also plotted for reference.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The performance of the proposed and spectrum averaging schemes was shown when they are using a 1000 MHz bandwidth with = 3.6 GHz, while Silva's method was presented at several frequencies since it is a narrowband-based angle estimation. The performance bound calculated from the Cramér-Rao bound (CRB) when the DOD and DOA of a stationary target are estimated individually [26,27] was also plotted for reference.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…By inserting (5) into (10), and exploiting the property Q y = J MN Q y *J MN characteristic of Hermitian symmetric Toeplitz matrix Q y , we have…”
Section: Covariance Differencingmentioning
confidence: 99%
“…The peak search methods, such as Capon‐based algorithm [6] and MUSIC‐based [7] algorithm, are first introduced to bi‐static MIMO radar. Then, reduced‐Capon [8], reduced‐MUSIC [9] and expectation‐maximisation (EM) maximum‐likelihood (ML) algorithms [10] are proposed to reduce the multi‐dimensional searching load. To bypass searching process, polynomial root MUSIC algorithm, DOA matrix method, estimation of signal parameters by rotational invariance techniques (ESPRIT) algorithm and PARAFAC‐based technique are applied to bi‐static MIMO radar [11–14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these methods still have some weaknesses which limit their practical application. An EM ML algorithm of DOA estimation for bistatic Multiple-Input Multiple-Output (MIMO) radar is present in [13], where it is shown that the DOA estimation problem can be described as a special case of ML estimation with incomplete data. Simulation results demonstrate the potential and asymptotic efficiency of this approach for MIMO radar systems.…”
Section: Introductionmentioning
confidence: 99%